The effects of sugar addiction on health and the importance of exercise - Kwaśniak, Ksenia; Magierska, Agata; Foryś, Angelika; Miłek, Magdalena; Banach, Mariola; Ślusarczyk , Monika; Stawska, Weronika; Niemczyk, Anna; Kmiotek, Weronika; Kotowicz, Zuzanna (Quality in Sport, 2024)
Introduction and purpose: Sugar is the primary energy substrate for the brain. Consuming sweet products releases dopamine, which activates the reward system. In this aspect, excessive consumption of sugar is similar to drug use and leads to many health risks. The aim of the study is to systematize information on sugar addiction, highlight the need for preventive measures and create treatment algorithms covering areas such as psychotherapy, pharmacotherapy and the positive impact of physical activity. Materials and metods: A literature search was conducted using the medical databases PubMed and Google Scholar. Articles were retrieved in English, employing the key words: “sugar addiction”, “sweet taste”, „sugar diabetes” and „sugar sport” in appropriate configurations. The analysis encompassed data from 34 scientific references published between 2007 and 2024. Conclusions: Many factors contribute to sugar addiction. It is a self-perpetuating cycle, as obese and sugar addicts need more sugar to feel satisfied. At the same time, sugar negatively affects body weight, behavior, mood, cardiovascular, nervous, digestive systems. Which is why steps should be taken to increase public understanding and awareness of the mechanism of sugar addiction and its risks.